Hey can someone please help me out with this? I'll fan and medal :)
Write x^2 - 2x - 3 = 0 in the form (x - a)^2 = b, where a and b are integers.
(x - 4)^2 = 3
(x - 3)^2 = 2
(x - 2)^2 = 1
(x - 1)^2 = 4

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

@Vocaloid @iGreen @wio @Kainui

complete the square

do you know how to do that?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.